Muslim Women, Tradition, and Patriarchy: A Critical Study of the Manuscript Daf' al-Turrahāt 'an Wājibāt al-Ummahāt - Andhika Tiara; M. Adib Misbachul Islam; Safurotun Ziah (Indonesian Journal of Islamic Literature and Muslim Society, 2025)
This study aims to present a critical edition of the text Dafʿ al-Turrahāt ʿan Wājibāt al-Ummahāt (MDTWU) authored by Habib Salim bin Jindan and to analyze his views on Muslim women. MDTWU was written as a response to Qasim Amin’s work, Taḥrīr al-Marʾah. This qualitative study employs a philological approach and intertextual theory. The philological method is applied to produce a readable and comprehensible text, while the intertextual approach is used to trace the interrelations between texts.The findings reveal that MDTWU is a codex unicus—the only known manuscript—preserved in a private collection at the Al-Fachriyah Foundation Library in Tangerang, Banten. Despite its limited circulation and the absence of printed editions, MDTWU provides an important contribution to the discourse on Muslim women in the 20th century. The analysis demonstrates that Habib Salim bin Jindan’s views are largely shaped by patriarchal constructions, emphasizing the preservation of traditional values amid modernization so that women may maintain their rights without losing their identity and dignity. The study further highlights the contrast with Qasim Amin’s perspective, which rejects the traditional confinement of women to the domestic sphere and interprets oppressive values as cultural constructs rather than authentic Islamic teachings. This study supports the findings of Tohari (2021) and Bachtiar (2023), which argue that women’s freedom should remain grounded in Islamic values as a source of legitimacy. Moreover, it suggests that Western-based concepts of women’s emancipation should be critically assessed to ensure their compatibility with Islamic ethical principles. Keywords: Philology, Muslim Women, Manuscript Daf’ al-Turrahāt ‘an Wājibāt al-Ummahāt, Habib Salim, Qasim Amin.